American Indian/Alaska Native and black colon cancer patients have poorer cause-specific survival based on disease stage and anatomic site of diagnosis. (October 2022) - Pankratz, V. Shane; Kosich, Mikaela; Edwardson, Nicholas; English, Kevin; Adsul, Prajakta; Li, Yiting; Parasher, Gulshan; Mishra, Shiraz I.
Abstract: Objectives: Studies of race-specific colon cancer (CC) survival differences between right- vs. left-sided CC typically focus on Black and White persons and often consider all CC stages as one group. To more completely examine potential racial and ethnic disparities in side- and stage-specific survival, we evaluated 5-year CC cause-specific survival probabilities for five racial/ethnic groups by anatomic site (right or left colon) and stage (local, regional, distant). Methods: We obtained cause-specific survival probability estimates from National Cancer Institute's population-based Surveillance, Epidemiology, and End Results (SEER) for CC patients grouped by five racial/ethnic groups (Non-Hispanic American Indian/Alaska Native [AIAN], Non-Hispanic Asian/Pacific Islander [API], Hispanic, Non-Hispanic Black [NHB], and Non-Hispanic White [NHW]), anatomic site, stage, and other patient and SEER registry characteristics. We used meta-regression approaches to identify factors that explained differences in cause-specific survival. Results: Diagnoses of distant-stage CC were more common among NHB and AIAN persons (>22 %) than among NHW and API persons (< 20 %). Large disparities in anatomic site-specific survival were not apparent. Those with right-sided distant-stage CC had a one-year cause-specific survival probability that was 16.4 % points lower (99 % CI: 12.2–20.6) than those with left-sided distant-stage CC; this difference decreased over follow-up. Cause-specific survival probabilities were highest for API, and lowest for NHB, persons, though these differences varied substantially by stage at diagnosis. AIAN persons with localized-stage CC, and NHB persons with regional- and distant-stage CC, had significantly lower survival probabilities across follow-up. Conclusions: There are differences in CC presentation according to anatomic site and disease stage among patients of distinct racial and ethnic backgrounds. This, coupled with the reality that there are persistent survival disparities, with NHB and AIAN persons experiencing worse prognosis, suggests that there are social or structural determinants of these disparities. Further research is needed to confirm whether these CC cause-specific survival disparities are due to differences in risk factors, screening patterns, cancer treatment, or surveillance, in order to overcome the existing differences in outcome. Highlights: AIAN and NHB persons are more often diagnosed with colon cancer at distant summary stages than are API and NHW persons. AIAN and NHB persons have lower 5-year CC-specific survival than API, Hispanic, and NHW persons for multiple summary stages. Patterns of CC-specific survival are distinct among racial and ethnic groups according to the stage at cancer diagnosis. There are different patterns of CC-specific survival between left- and right-sided CC according to the stage at diagnosis.